Influence of rice flour on conformational changes in the dough during production of wheat bread - Shevchenko, Anastasiia; Litvynchuk (Vorontsova), Svitlana (My University, 2022)
The aim of the work was to determine the influence of rice flour on the conformational transformations in the structure of the dough for the production of wheat bread, which contains lecithin. The fractional composition of proteins showed a higher content of albumin, prolamin and insoluble proteins in wheat flour than in rice flour by 11, 90 and 75%, respectively. The content of globulins and glutelins is more in rice flour by 7 and 183%, respectively, but the composition of glutelins in the studied samples is different. In wheat flour, it is glutenin, which is a gluten protein, forming a heterogeneous mixture of polymers through disulfide bonds of polypeptides. In rice flour, oryzenin is a representative of glutelins. The infrared reflection spectra of wheat and rice flour showed a similar nature of the spectra: the extremes are observed at the same wavelengths, the spec-tra are located parallel to each other and differ only in the intensity of reflection. The spectrum of sunflower lecithin differs significantly due to its different chem-ical composition. Also, at some wavelengths on the spectrum of lecithin, extreme shifts in both short and long wavelength regions are visible. The secondary structure of gluten underwent changes in bread after exposure to temperature by promoting α-helices and β-turns and contributed to the formation of disulfide bonds.
Keywords: bread; rice; flour; lecithin; IR spectroscopy; кафедра технології хлібопекарських і кондитерських виробів; кафедра фізики та професійної безпеки